Developing Android Application To Guide Lean Six Sigma PDCA Project - Ong, Sin Joo (Universiti Sains Malaysia, 2018)
The knowledge of Lean Six Sigma can be learned through online training, university course and company training program. There is no existing guideline available for practitioner to carry out the Plan-Do-Check-Act (PDCA). This often leads to confusions and misuse of lean tools. Mobile application grows rapidly with abundant of application development. This research aims to develop an Android-based approach to provide guidelines of PDCA. Massachusetts Institute of Technology (MIT) App Inventor was selected as the application development platform. Guidelines to PDCA, including the associated lean tools for different stages were collected from the literature review. The graphical user interface was designed by follow with application algorithm. Testing of the application was conducted on seven projects from six yellow belt and four advanced lean students. The results obtained through the system usability scale (SUS) survey were analyzed and discussed. The SUS score obtained from the seven projects were in a range of 52.5 to 67.5 which considered as a moderate system and seek for improvement. Improvements were made accordingly. As the practical contribution, the work produces a ready to use mobile application to help practitioners in particular those in the industry at the early stage of lean journey. The mobile application provides guidance for them to ensure methodological problem solving. Some recommendations were suggested for future development.